Web interactive multimedia technology: implementation from two perspectives - Md Ali, Asma; Richardson, Joan (The Society of Digital Information and Wireless Communications, 2012)

(untitled)
Web interactive multimedia technology (WIMT), which is an information and communication system, was introduced in a large metropolitan university. Its features are outlined in this paper, from simply textbased to more complex. The system incorporates several interactive and multimedia features, such as chat, audio, video, polling, whiteboard and desktop sharing. This system provides real time collaboration. When used in a university teaching and learning environment, it enables immediate feedback between participants across physical space. This provides opportunities in a web learning environment, for interactivity and relationship building between academics and students, a vital component of learning. WIMT implementation in real context is being studied from two perspectives, the academic developer and academic lecturer. The lessons learned are also being identified and documented to be shared.